Differences between the catalase isozymes of maize (Zea mays L.) in respect of inhibition by various phenolic compounds - Horváth, Eszter (Acta Biologica Szegediensis, 2002)
Catalase isozymes of maize (Zea mays, L. hybrid Norma) were shown to differ in their sensitivity to phenolic compounds. Salicylic acid, benzoic acid, acetylsalicylic acid and o-coumaric acid caused significantly greater inhibition of CAT1 activity than of CAT2. The nature of inhibition was non-competitive for CAT1, while CAT2 was inhibited competitively. P-hydroxybenzoic acid (pHBA) was the only compound to inhibit both CAT1 and CAT2 activity in the same competitive manner. pHBA was also the only phenolic compound examined that failed to induce chilling tolerance in young maize plants. According to these results, CAT1 might be a candidate for mediating the effect of SA on the induction of chilling tolerance in maize.